Environmental control of carbon allocation matters for modelling forest growth - Guillemot, Joannès; Francois, Christophe; Hmimina, Gabriel; Dufrêne, Eric; Martin‐StPaul, Nicolas K.; Soudani, Kamel; Marie, Guillaume; Ourcival, Jean‐Marc; Delpierre, Nicolas (The New phytologist, 2017)
We aimed to evaluate the importance of modulations of within-tree carbon (C) allocation by water and low-temperature stress for the prediction of annual forest growth with a process-based model. A new C allocation scheme was implemented in the CASTANEA model that accounts for lagged and direct environmental controls of C allocation. Different approaches (static vs dynamic) to modelling C allocation were then compared in a model–data fusion procedure, using satellite-derived leaf production estimates and biometric measurements at c. 104 sites. The modelling of the environmental control of C allocation significantly improved the ability of CASTANEA to predict the spatial and year-to-year variability of aboveground forest growth along regional gradients. A significant effect of the previous year’s water stress on the C allocation to leaves and wood was reported. Our results also are consistent with a prominent role of the environmental modulation of sink demand in the wood growth of the studied species. Data available at large scales can inform forest models about the processes driving annual and seasonal C allocation. Our results call for a greater consideration of C allocation drivers, especially sink–demand fluctuations, for the simulations of current and future forest productivity with process-based models.